2015
DOI: 10.2147/ijn.s77268
|View full text |Cite
|
Sign up to set email alerts
|

A novel nanobody specific for respiratory surfactant protein A has potential for lung targeting

Abstract: Lung-targeting drugs are thought to be potential therapies of refractory lung diseases by maximizing local drug concentrations in the lung to avoid systemic circulation. However, a major limitation in developing lung-targeted drugs is the acquirement of lung-specific ligands. Pulmonary surfactant protein A (SPA) is predominantly synthesized by type II alveolar epithelial cells, and may serve as a potential lung-targeting ligand. Here, we generated recombinant rat pulmonary SPA (rSPA) as an antigen and immunize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Another example for the use of nanobodies in the development of lung-targeting drugs is the targeting of pulmonary surfactant protein A (SPA) [115]. Due to the exclusive expression of SPA on alveolar epithelial type II cells, it can serve as a molecule for specific targeting of lung diseases.…”
Section: Nanobodies Against Lung Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example for the use of nanobodies in the development of lung-targeting drugs is the targeting of pulmonary surfactant protein A (SPA) [115]. Due to the exclusive expression of SPA on alveolar epithelial type II cells, it can serve as a molecule for specific targeting of lung diseases.…”
Section: Nanobodies Against Lung Diseasesmentioning
confidence: 99%
“…Due to the exclusive expression of SPA on alveolar epithelial type II cells, it can serve as a molecule for specific targeting of lung diseases. In one study, the authors selected two nanobodies, Nb6 and Nb17, that showed high specificity for SPA [115]. To evaluate the lung-targeting ability of Nb17, the authors performed in vivo imaging using murine models and showed fast accumulation of Nb17 in the lungs, and complete clearance from the blood circulation within 6 h after injection.…”
Section: Nanobodies Against Lung Diseasesmentioning
confidence: 99%
“…In our previous study, we successfully constructed an Nb library for rat pulmonary surfactant protein A and identified Nb17 as a specific Nb for rat pulmonary SP-A. Nb17 is very specific, shows high affinity to the target protein, and has a satisfactory safety profile 22 . The current study was based on our previous experience on Nb17 and took the advantages of the very high homology (98%) of rat and human pulmonary SP-A protein to identify Nb4, which specifically binds human pulmonary SP-A.…”
Section: Discussionmentioning
confidence: 99%
“…Human pulmonary tissue frozen sections were used for biopanning of our previously constructed phage-display Nb library 22 . The frozen tissue sections were washed 10 times with sterile PBS and then incubated with 2 mL solution containing the Nb library at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, to develop lung-targeting drugs, Nbs targeting pulmonary surfactant protein A (SPA) have been isolated. The authors showed fast accumulation of selected Nbs in the lungs (Wang et al 2015). Nbs against different coronavirus species have been isolated and characterized to block interaction between virus and host cell.…”
Section: Neutralizing Vhh Against Viral Zoonosismentioning
confidence: 99%